(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The importance of self-help projects on community development cannot overstressed. It has become one of the development approaches that have improved the social and economic wellbeing of rural dwellers, especially the development of infrastructure. This study is aimed at examining self-help projects and community development in Oruk-Anam Local Government Area of Akwa Ibom State, Nigeria. The study hypothesized that there is no significant relationship between road construction projects and community development and that there is no significant relationship between healthcare facilities and community development. The system theory forms the theoretical framework for the study. With an expo facto research design, Taro Yamane sampling framework was used to select forty (40) households as the respondents for the study. The data obtained from the instrument was tested using the Pearson Product Moment Correlation Analysis. The result of data analysis showed that the hypotheses were rejected and the alternate accepted. The implication is that self-help projects; road constructions and the provision of health care facilities significantly affect community development. The study recommends that there is a need for the government and corporate organizations to complement community efforts by providing infrastructure in rural communities. This is believed will support economic activities in the area.